Initiation of breastfeeding within 120 minutes after birth is associated with breastfeeding at four months among Japanese women: A self-administered questionnaire survey - Moji Kazuhiko; Nakao Yuko; Honda Sumihisa; Oishi Kazuyo (BMC, 2008)
Abstract Background The proportion of mothers in Japan who breastfeed exclusively has been low since the 1970s. The purpose of this study was to examine the association between the time of first breastfeed after birth and the proportion of mothers fully breastfeeding up to four months postpartum. Methods A survey was conducted using a self-administered questionnaire. The participants were 318 mothers who participated in a physical examination of their four month old infants in Nagasaki City, Japan in 2003. Results The time of first breastfeeding up to 120 minutes was significantly associated with the proportion of mothers fully breastfeeding during their stay in the clinic/hospital (p = 0.006), at one month (p = 0.004) and at four months after birth (p = 0.003). There was no significant difference in the proportion of full breastfeeding in mothers who first breastfed between the period of less 30 minutes after birth and that of between 31 and 120 minutes after birth. Logistic regression analysis indicated that the proportion of mothers who continued full breastfeeding at four months was significantly higher in those who breastfed their baby within 120 minutes compared with more than 120 minutes (OR 2.5, p = 0.01), but was not significantly different in those who breastfed within 30 minutes compared with more than 30 minutes (OR 1.8, p = 0.06). Early breastfeeding was affected by caesarean section, premature delivery and severe bleeding during delivery. Conclusion Commencement of early breastfeeding was associated with the proportion of mothers who fully breastfed their infants up to four months. Early breastfeeding, especially within two hours, is recommended for child and maternal health.